Formulating Business Development Strategies through SWOT Analysis: A Case Study of Kayffa Store - Dwi Anggraeni; Rita Mutiarni (Proceeding International Conference on Digital Education and Social Science, 2025)
Micro, small, and medium enterprises (MSMEs) face increasing competitive pressure that requires the formulation of effective and adaptive business strategies. This study aims to analyze the internal and external conditions of Kayffa Store and to formulate appropriate business development strategies using an integrated SWOT analysis approach. A descriptive qualitative method was employed, with data collected through observation, interviews with the business owner, and documentation. The analysis was supported by the Internal Factor Evaluation (IFE) Matrix, External Factor Evaluation (EFE) Matrix, Internal–External (IE) Matrix, and Grand Strategy Matrix. The results indicate that Kayffa Store possesses several internal strengths related to product quality and customer trust, while weaknesses are identified in marketing management and promotional activities. The integration of internal and external factors places the enterprise in a moderate strategic position, suggesting a hold-and-maintain strategy. The study concludes that strengthening internal capabilities and selectively utilizing market opportunities are essential for sustainable business development.